Metal-ligand cooperativity of the calix(4)pyrrolato aluminate: triggerable C-C bond formation and rate control in catalysis - Ebner, Fabian; Sigmund, Lukas M.; Greb, Lutz (Angewandte Chemie, 2020)
Metal-ligand cooperativity (MLC) had a remarkable impact on transition metal chemistry and catalysis. By use of the calix[4]pyrrolato aluminate, [1]−, which features a square-planar AlIII, we transfer this concept into the p-block and fully elucidate its mechanisms by experiment and theory. Complementary to transition metal-based MLC (aromatization upon substrate binding), substrate binding in [1]− occurs by dearomatization of the ligand. The aluminate trapps carbonyls by the formation of C−C and Al−O bonds, but the products maintain full reversibility and outstanding dynamic exchange rates. Remarkably, the C−C bonds can be formed or cleaved by the addition or removal of lithium cations, permitting unprecedented control over the system's constitutional state. Moreover, the metal-ligand cooperative substrate interaction allows to twist the kinetics of catalytic hydroboration reactions in a unique sense. Ultimately, this work describes the evolution of an anti-van't Hoff/Le Bel species from their being as a structural curiosity to their application as a reagent and catalyst.
Im Titel steht die 4 in eckiger Klammer
First published: 23 June 2020
Gesehen am 02.11.2021